Fruit Development in Ficus carica L.: Morphological and Genetic Approaches to Fig Buds for an Evolution From Monoecy Toward Dioecy - Marcotuli, Ilaria; Mazzeo, Andrea; Colasuonno, Pasqualina; Terzano, Roberto; Nigro, Domenica; Porfido, Carlo; Tarantino, Annalisa; Aiese Cigliano, Riccardo; Sanseverino, Walter; Gadaleta, Agata; Ferrara, Giuseppe (Frontiers in Plant Science, 2020)
The mechanism behind the bud evolution towards breba or main crop in Ficus carica L. is uncertain. Anatomical and genetic studies may put a light on the possible similarities/differences between the two types of fruits. For this reason, we collected complimentary data from anatomical, X-ray imaging, and genetic techniques. The RNA seq together with structural genome annotation allowed the prediction of 34,629 known genes and 938 novel protein-coding genes. Transcriptome analysis of genes during bud differentiation revealed differentially expressed genes in two fig varieties (Dottato and Petrelli) and in breba and main crop. We chose Dottato and Petrelli because the first variety does not require pollination to set main crop and the latter does; moreover, Petrelli yields many brebas whereas Dottato few. Of the 1,615 and 1,904 loci expressed in Dottato and Petrelli, specifically in breba or main crop, respectively, only 256 genes appeared to be transcripts in both varieties. The buds of the two fig varieties were observed under optical microscope and using 3D X-ray tomography, highlighting differences mainly related to the stage of development. The X-ray images of buds showed a great structural similarity between breba and main crop during the initial stages of development. Analysis at the microscope indicated that inflorescence differentiation of breba was split in two seasons whereas that of main crop started at the end of winter of season 2 and was completed within 2 to 3 months. The higher expression of floral homeotic protein AGAMOUS in breba with respect to main crop, since this protein is required for normal development of stamens and carpels in the flower, may indicate an original role of these fruits for staminate flowers production for pollination of the main crop, as profichi in the caprifig. Several genes related to auxin (auxin efflux carrier, auxin response factor, auxin binding protein, auxin responsive protein) and to GA synthesis (GA20ox) were highly expressed in brebas with respect to main crop for the development of this parthenocarpic fruit.